Structural and functional characterization of Group B Streptococcus class C sortases - Cozzi, Roberta <1981> (Alma Mater Studiorum - Università di Bologna, 2011)
In Group B Streptococcus (GBS) three structurally distinct types of pili have been discovered as potential virulence factors and vaccine candidates. The pilus-forming proteins are assembled into high-molecular weight polymers via a transpeptidation mechanism mediated by specific class C sortases. Using a multidisciplinary approach including bioinformatics, structural and biochemical studies and in vivo mutagenesis we performed a broad characterization of GBS sortase C. The high resolution X-ray structure of the enzymes revealed that the active site, located into the β-barrel core of the enzyme, is made of the catalytic triad His157-Cys219-Arg228 and covered by a loop, known as the “lid”. We show that the catalytic triad and the predicted N- and C-terminal trans-membrane regions are required for the enzyme activity. Interestingly, by in vivo complementation mutagenesis studies we found that the deletion of the entire lid loop or mutations in specific lid key residues had no effect on catalytic activity of the enzyme. In addition, kinetic characterizations of recombinant enzymes indicate that the lid mutants can still recognize and cleave the substrate-mimicking peptide at least as well as the wild type protein.